The habit of critical thinking has to be cultivated and I think we have to safeguard this competence: Sandra Marinho, Professor of Journalism and Communication Sciences - Bonixe, Luis (Aprender, 2023)
Sandra Marinho holds a PhD in Communication Sciences, in the area of ​​Journalism Studies, from the University of Minho. She is a professor at the same institution, where she has taught in the areas of Research Methodologies and Journalism. She is a researcher at CECS (Center for Studies on Communication and Society), where she conducts research on the quality of journalism/information/communication and on the quality of journalism teaching. He has participated in several research projects (national and international). She was director of the Degree and Masters in Communication Sciences at UMinho and was coordinator of the REC | Reporters in Construction, of which she is also one of the founders. She was deputy director of CECS and is part of the Executive Committee of the IDEA-UMinho Centre, the structure that promotes the strategy of pedagogical innovation and development of skills in the teaching ecosystem of the University of Minho.
Keywords: training; journalism; technology; Portugal